S100A6 and c-Kit-Positive Spindle Cell Melanoma of the Dorsal Foot - Yasutaka Mitamura; Takamichi Ito; Misa Nakano-Nakamura; Hiroshi Uchi; Masutaka Furue (Karger Publishers, 2014)
Spindle cell melanoma, which is a rare form of melanoma, is clinically and histopathologically difficult to diagnose from a variety of nonmelanocytic spindle cell tumors. We describe a 42-year-old Japanese woman with amelanotic melanoma that comprised spindle cells with positive c-kit and S100A6 staining. The use of c-kit and S100A6 might be useful for improving the diagnosis.